The Relationship between Other Comprehensive Income and Earnings Management: Evidence from the Stock Exchange of Thailand - Sabsombat, Nuthawut (Asian Administration and Management Review, 2019)
This research aims to examine the relationship between other comprehensive income (OCI) and earnings management (EM). The population in the study are the firms registered in the Stock Exchange of Thailand between 2011 and 2017. The statistical techniques consist of both descriptive statistics and inferential statistics. The study discovers a significant negative relationship between OCI and EM, where a firm which reports a high OCI sees a decrease in EM conducted by the firm executives. Such finding demonstrates that if OCI is reported correctly and comprehensively, then users of the financial statements are more confident that the firm has shown truthful accounting information in compliance with the accounting principles. It also reflects the firm’s transparency, reduces the degree of asymmetric information between principals and agents, and reduces the opportunity of EM, which improves the earnings quality of the firm.